Relationship Between the Health Belief Model and Dietary Patterns Among Fishermen in Pangandaran - Kenita Amelia Fernanda; Sheizi Pristasari; Siti Ulfah Rifa'atul Fitri (Jurnal Kesehatan Budi Luhur: Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2026)
Fishermen are a group of workers with long working hours and irregular working conditions, which can potentially affect their health behaviors, particularly their dietary patterns. The dietary patterns of fishermen in the Pangandaran coastal area tend to be irregular due to heavy workloads, time constraints, and limited access to nutritious food while at sea. The Health Belief Model (HBM) explains that health behavior is influenced by individuals' perceptions of susceptibility, severity, benefits, and barriers. This study aimed to examine the relationship between Health Belief Model beliefs and the dietary patterns of fishermen in the Pangandaran coastal area. This study employed a quantitative descriptive design with a cross-sectional approach. The study population consisted of fishermen at Cikidang Port, Pangandaran, with a sample of 126 respondents selected through simple random sampling. Dietary patterns were measured using the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), while health beliefs were measured using a Health Belief Model questionnaire covering perceptions of susceptibility, severity, benefits, and barriers. Data were analyzed using univariate and bivariate analyses with correlation tests. The results showed that most fishermen had poor dietary patterns, while the majority of respondents had high perceptions of susceptibility, severity, and benefits, as well as low perceptions of barriers. Bivariate analysis found no relationship between the four components of the Health Belief Model and fishermen's dietary patterns. These findings indicate that high health beliefs are not necessarily accompanied by healthy dietary behaviors and suggest that factors such as working conditions, limited access to food, and the lack of integration of self-efficacy and cues to action may also influence dietary patterns.